"H Newman" and Ludwig Wittgenstein: Re‐evaluating the History of John Henry Newman's Philosophical Reception. (11th December 2019) - Pratt Morris‐Chapman, Daniel
Abstract: It is commonly held that that the dominance of logical positivism, in the early part of the twentieth‐century, hindered Newman's philosophical recognition. However, commentators also argue that Newman's writing began to gain wider recognition following Wittgenstein's reference to "H Newman" (1969) in the posthumous publication of On Certainty. This essay explores whether or not this version of the history of Newman's philosophical reception rings true – exploring whether or not the reference to "H Newman" really marks a watershed for Newman's philosophical legacy.